1997
DOI: 10.1080/00085030.1997.10757103
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of Occurrence of Paint and Glass on the Clothing of High School Students

Abstract: The frequency of occurrence of paint chips and glass fragments on the outer clothing and footwear of 213 high school students from different areas of the city of Vancouver was determined. Paint and glass respectively were found on ca. 14% and 2% of the outer clothing items, and on ea, 24% and 5% of footwear. These figures are significantly lower than figures reported in similar studies in the last 25 years. RESUMELa frequence avec laquelle des ecailles de peinture et des fragments de verre se retrouvent sur le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 1 publication
2
12
0
Order By: Relevance
“…No broken glass Broken glass Petterd et al [10] Lau et al [11] McQuillian et al [8] Ross et al [13] Coulson et al [9] Lambert et al [ reported in previous studies, however the numbers of fragments within individual groups present were more akin to data produced from studies involving individuals suspected of activities involving broken glass.…”
Section: Population (P) Suspects General Population This Studymentioning
confidence: 65%
See 2 more Smart Citations
“…No broken glass Broken glass Petterd et al [10] Lau et al [11] McQuillian et al [8] Ross et al [13] Coulson et al [9] Lambert et al [ reported in previous studies, however the numbers of fragments within individual groups present were more akin to data produced from studies involving individuals suspected of activities involving broken glass.…”
Section: Population (P) Suspects General Population This Studymentioning
confidence: 65%
“…A summary of comparisons to the studies of McQuillian et al [8], Coulson et al [9], Pettard et al [10], Lau et al [11], Lambert et al [12] and Ross et al [13] is presented in Table 3.…”
Section: Comparisons Of All Fleeces Examined With Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Equation (4) in Example 1 contains a number of quantities that must be estimated. The P terms and S terms, relating to the size and number of recovered groups, can be estimated via clothing surveys (Pearson et al, 1971;McQuillan & McCrossan, 1987;McQuillan & Edgar, 1992;Lambert et al, 1995;Lau et al, 1997;Coulson et al, 2001). Coulson et al (2001) have devoted considerable effort in the statistical modelling of the P and S terms concerning the number and size of groups of glass found on clothing.…”
Section: Estimation Of Background and Transfer Probabilitiesmentioning
confidence: 99%
“…A study by and Lau et al [4] examined clothing and footwear for glass and paint. Only one fragment was found in the pockets searched.…”
Section: Introductionmentioning
confidence: 99%